Metáforas do casamento no discurso religioso - Costa, Carla Nascimento da (2010)
This dissertation aims at investigating, in a corpus in English, metaphoric expressions present in an argumentative genre, the religious sermon , to refer to the instituition of marriage , reflecting upon the conceptual metaphors that would license the use of these expressions by the participantes of the discourse community being investigated, as well as the persuasive intentions of the speaker of this text genre. Our assumption is that this speaker has made use of metaphoric expressions in order to build his argumentation during the religious sermon, in an attempt to make the persuasion of the listeners more effective. The study is based on two theoretical axes: theories of religious discourse (ORLANDI, 1984, 1987) and theories of metaphor, focusing mostly on the principles of the socio - cognitive theory (LAKOFF, JOHNSON, [1980]2002; LAKOFF, TURNER, 1999), the relationship between metaphor and culture (KÖVECSES, 2002, 2005, 2007), with persuasion and ideology (CHARTERIS-BLACK, 2004; GOATLY, 2007; LAKOFF, 1996), as well as with discourse (CAMERON, 2008; CHARTERIS-BLACK, 2005; MUSOLFF, 2004; SEMINO, 2008; VEREZA, 2007, 2010). The methodology adopted is qualitative. The corpus used was transcriptions of religious sermons of Protestant Christian churches. The analysis of the data has shown, among other aspects, that the speaker of the text-genre religious sermon uses various metaphoric expressions to refer to the institution of marriage, aiming at teaching his listeners, the Protestant Christian believers, how to act, in their everyday lives, in relation to their marriages, following the biblical principles taught.